INFORMATION TECHNOLOGY INVESTMENT BENEFIT ANALYSIS SATELLITE T3S AT PT TELKOM INDONESIA (PERSERO) TBK - I Gusti Ayu Made Nindya Parmitasuari; Ni Made Estiyanti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The development of information technology in Indonesia still needs to be felt thoroughly by the public. This is due to the geographical condition of Indonesia, which consists of islands, so the optical cable network still needs to reach remote areas, especially the 3T (Outermost, frontier and disadvantaged) areas. As a result, many people need access to the internet. To overcome this, PT Telkom Indonesia (persero) Tbk invested in IT in the satellite sector. The Telkom 3S satellite will be able to help the company in reaching more users in remote areas. This study aims to find out what benefits the company gets after making satellite investments, which can later help companies in evaluating satellite investments. The method uses three methods to analyze the benefits of information technology investment: the financial statement comparison, cost-benefit, and Ranti's Generic IS / IT Business Value. Using these three methods, analysis of the benefits of technology investment resulted in Telkom 3S satellite investment bringing benefits to its finances, employees and customers.